A multi-pronged approach to effective application security. Issue 8 (August 2021) - Valani, Altaz
Abstract : Cyber security has become one of the main pillars of a successful business, especially when you factor in elements such as business innovation, operations and risk management – all of which require adequate security to work. Therefore, investing in adequate cyber security infrastructure and tools is vital for organisations looking to scale and remain competitive.